Exploration of emotional and psychosocial responses following initial HIV Diagnosis: A qualitative study - Untung Sujianto; Ikhwan Amirudin; Azizati Salmas Marsiami; Achmad Fauji (School of Health Sciences Al-Ma'arif, 2026)
Background: Receiving an initial HIV diagnosis is often accompanied by profound emotional disruption, psychosocial uncertainty, stigma-related concerns, and challenges in disclosure and early treatment engagement. Although previous studies have examined HIV adherence, stigma, and treatment outcomes, limited evidence describes the immediate emotional and psychosocial responses experienced by newly diagnosed adults during the first months of HIV care, particularly in local healthcare settings in Indonesia. Objective: This study aimed to explore emotional and psychosocial responses following an initial HIV diagnosis among individuals receiving early HIV care in urban and rural healthcare facilities in Pringsewu, Lampung Province, Indonesia. Methods: A qualitative descriptive design was used. Participants were recruited purposively from healthcare facilities providing HIV counseling, testing, and antiretroviral therapy services. Fifteen adults diagnosed with HIV within one to seven months before data collection participated in face-to-face, in-depth semi-structured interviews. Data were collected in private rooms to ensure confidentiality and emotional safety. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Trustworthiness was strengthened through participant validation, audit trail documentation, reflective notes, team discussions, and the use of representative quotations. Results: Thematic analysis generated three major themes. The first theme, emotional shock and personal crisis after HIV diagnosis, reflected participants’ disbelief, fear of death, uncertainty about the future, guilt, and self-blame. The second theme, stigma and fear of social reactions, described fear of family rejection, concealment of HIV status as self-protection, workplace concerns, and internalized stigma. The third theme, early adaptation and emerging hope for survival, showed gradual acceptance, reliance on support from healthcare providers or significant others, and commitment to antiretroviral therapy. These findings indicate a transition from emotional crisis and social fear toward early coping, acceptance, and treatment commitment. Conclusion: Newly diagnosed individuals experience complex emotional and psychosocial responses during the early phase of HIV care. Integrating stigma reduction, emotional counseling, accurate health information, and supportive care into HIV services may strengthen adaptation, disclosure readiness, and long-term treatment engagement among people newly diagnosed with HIV.